Unjuk Rasa Versus Menghujat (Perspektif Hukum islam) - Rahman, Muhammad Gazali (Alhurriyah, 2013)
This papers is reviewing about the phenomenon of demonstration versus blaspheming that analyzed in descriptive with Islamic law approach. This analysis was then developed on two issues, there are: 1) how the phenomenon of demonstrartion and blaspheming; 2) how the perspective of Islamic law on demonstration and blaspheming. Although it can not be generalized, reality at every demonstration activities, the dirty words seem to have become an obligatory song, that should be sung with full of spirit as a the media to berate, incite, blaspheming, even less to provoking, until culminate in anarchy. When it has been so, the democracy lessons, morals, and manners that were taught in school no longer seemed meaningful at all. This is ironic if in these circumstances there is still some that say â€œthis is a political education!â€. Even, this demonstration phenomenon is not only happening at the level of college, but also has happened in the institutions of formal education providers secondary level (high school or vocational school). School that should be the development of a positive culture center changed becoming the showground of articulation of words that extremely far from the polite category.